The Continuous Monitoring of Selected Railway Structures using the Autonomous Data Logger - Dusan Janostik; Viktor Nohal; Herbert Seelmann; Jaroslav Smutny (Communications - Scientific letters of the University of Zilina, 2020)
This contribution focuses on issue of the autonomous monitoring of selected dynamic parameters of the railway lines test sections under conditions in the Czech Republic. Description of the possibilities of such data collection, including the designed hardware and software, is a part of this contribution. At the same time, the contribution describes application of such a measuring system, comparing the selected dynamic parameters of the two types of switches, the first one was a switch with a standard fastening node, the other one with an elasticized fastening node. Recommendations and conclusions of railway infrastructure manufacturers and railway line managers are parts of this contribution, as well.